ASHRAE global thermal comfort database ii: thermal comfort of mechanically ventilated and naturally ventilated office building - Aidil, Nur Muhammad; Hariri, Azian (Penerbit UTHM, 2021)
Thermal comfort is vital in office building for work performance improvement. This paper compares the thermal comfort in the naturally ventilated and mechanically ventilated office building in tropical wet Savanna (India) and winter Mediterranean climates (United Kingdom). The data was retrieved from the ASHRAE Global Thermal Comfort Database II and statistically analyzed by SPSS. Total of 160 samples were retrieved from the database and the correlation between thermal comfort parameters with PMV index value and linear regression analysis was conducted. Results of the study shows that for the naturally ventilated office, the thermal comfort temperature range was between 22.60℃ to 25.47℃ for India and wider range of 17.47℃ to 24.38℃ for the United Kingdom. On the other hand, the thermal comfort temperature range for a mechanically ventilated office in India was between 26.16℃ to 27.06℃ while for the United Kingdom, was between 20.63℃ to 24.94℃. In conclusion, wider thermal comfort range was found in the United Kingdom for both type of office ventilation especially for the naturally ventilated office. This was in the same agreement with the lower level or relative humidity, air velocity and higher clothing insulation value among the United Kingdom respondent.